The Ethnobotany Study of Medicinal Plants in Lombok Island - Damayanti, Riska; umami, sri sofiati; Suhirman, Suhirman (Universitas Islam Negeri Mataram, 2021)
Lombok has the biodiversity plant potential that can be used as medicine. This study aimed to identify the types of medicinal plants used by Sasak people, how to obtain, the parts used, how to use and processing, and the Species Use Value (SUV), Family Use Value (FUV), and Fidelity Level (FL). The results showed that there were 84 species used as traditional medicine by Lombok people. The method of obtaining medicinal plants was mostly done by cultivation, as much as 58% of the processing methods, and the most common use of plants in medicine was boiling and drinking. Plant species that had the highest SUV value were Morinda citrofolia, Zingiber officinale, and Elephantopus scaber with SUVs of 0.8 each. The plant family that had the highest FUV value was Zingiberaceae (eight species), furthermore, the part of the plant that had the highest value was the leaf. The total of plant species that had the highest Fidelity level was 52. One of them was celery (Apium graveolens L.). The data obtained from this research was needed to create an inventory of medicinal plant species and their use by the community, so that traditional knowledge of medicinal plants could be documented and preserved.